Lung cancer in patients with idiopathic pulmonary fibrosis: A retrospective multicentre study in Europe. Issue 1 (18th September 2022) - Karampitsakos, Theodoros; Spagnolo, Paolo; Mogulkoc, Nesrin; Wuyts, Wim A.; Tomassetti, Sara; Bendstrup, Elisabeth; Molina‐Molina, Maria; Manali, Effrosyni D.; Unat, Ömer Selim; Bonella, Francesco; Kahn, Nicolas; Kolilekas, Lykourgos; et al.
Abstract: Background and Objective: There remains a paucity of large databases for patients with idiopathic pulmonary fibrosis (IPF) and lung cancer. We aimed to create a European registry. Methods: This was a multicentre, retrospective study across seven European countries between 1 January 2010 and 18 May 2021. Results: We identified 324 patients with lung cancer among 3178 patients with IPF (prevalence = 10.2%). By the end of the 10 year‐period following IPF diagnosis, 26.6% of alive patients with IPF had been diagnosed with lung cancer. Patients with IPF and lung cancer experienced increased risk of all‐cause mortality than IPF patients without lung cancer (HR: 1.51, [95% CI: 1.22–1.86], p < 0.0001). All‐cause mortality was significantly lower for patients with IPF and lung cancer with a monocyte count of either <0.60 or 0.60–<0.95 K/μl than patients with monocyte count ≥0.95 K/μl (HR [<0.60 vs. ≥0.95 K/μl]: 0.35, [95% CI: 0.17–0.72], HR [0.60–<0.95 vs. ≥0.95 K/μl]: 0.42, [95% CI: 0.21–0.82], p = 0.003). Patients with IPF and lung cancer that received antifibrotics presented with decreased all cause‐mortality compared to those who did not receive antifibrotics (HR: 0.61, [95% CI: 0.42–0.87], p = 0.006). In the adjusted model, a significantly lower proportion of surgically treated patients with IPF and otherwise technically operable lung cancer experienced all‐cause mortality compared to non‐surgically treated patients (HR: 0.30 [95% CI: 0.11–0.86], p = 0.02). Conclusion: Lung cancer exerts a dramatic impact on patients with IPF. A consensus statement for the management of patients with IPF and lung cancer is sorely needed. Abstract : This is the largest study in Caucasian population showing that lung cancer is prevalent and exerts a dramatic impact on patients with idiopathic pulmonary fibrosis (IPF). Incidence of lung cancer increases over time in patients with IPF. Early identification and surgical resection might confer survival benefit. There remains substantial heterogeneity in disease management.